Diacylglycerol Kinase ζ (DGKζ) Is a Critical Regulator of Bone Homeostasis Via Modulation of c‐Fos Levels in Osteoclasts. (26th August 2015) - Zamani, Ali; Decker, Corinne; Cremasco, Viviana; Hughes, Lindsey; Novack, Deborah V; Faccio, Roberta
ABSTRACT: Increased diacylglycerol (DAG) levels are observed in numerous pathologies, including conditions associated with bone loss. However, the effects of DAG accumulation on the skeleton have never been directly examined. Because DAG is strictly controlled by tissue‐specific diacylglycerol kinases (DGKs), we sought to examine the biological consequences of DAG accumulation on bone homeostasis by genetic deletion of DGKζ, a highly expressed DGK isoform in osteoclasts (OCs). Strikingly, DGKζ ‐/‐ mice are osteoporotic because of a marked increase in OC numbers. In vitro, DGKζ ‐/‐ bone marrow macrophages (BMMs) form more numerous, larger, and highly resorptive OCs. Surprisingly, although increased DAG levels do not alter receptor activator of NF‐κB (RANK)/RANK ligand (RANKL) osteoclastogenic pathway, DGKζ deficiency increases responsiveness to the proliferative and pro‐survival cytokine macrophage colony‐stimulating factor (M‐CSF). We find that M‐CSF is responsible for increased DGKζ ‐/‐ OC differentiation by promoting higher expression of the transcription factor c‐Fos, and c‐Fos knockdown in DGKζ ‐/‐ cultures dose‐dependently reduces OC differentiation. Using a c‐Fos luciferase reporter assay lacking the TRE responsive element, we also demonstrate that M‐CSF induces optimal c‐Fos expression through DAG production. Finally, to demonstrate the importance of the M‐CSF/DGKζ/DAG axis on regulation of c‐Fos during osteoclastogenesis, we turned to PLCγ2 +/‐ BMMs, which have reduced DAG levels and form fewer OCs because of impaired expression of the master regulator of osteoclastogenesis NFATc1 and c‐Fos. Strikingly, genetic deletion of DGKζ in PLCγ2 +/‐ mice rescues OC formation and normalizes c‐Fos levels without altering NFATc1 expression. To our knowledge, this is the first report implicating M‐CSF/DGKζ/DAG axis as a critical regulator of bone homeostasis via its actions on OC differentiation and c‐Fos expression. © 2015 American Society for Bone and Mineral Research.